Praktik Bimbingan dan Konseling Islam dalam Pembinaan Akhlak Remaja di Komunitas Pedesaan: Bukti Empiris Dari Desa Tallung Ura: Islamic Guidance and Counseling Practices in Fostering Adolescents’ Moral Character in a Rural Community: Empirical Evidence from Tallung Ura Village - Ria Rezky Amir; Ruslan Ruslan; Amiruddin Z Nur (Dirasat Islamiah: Jurnal Kajian Keislaman, 2026)
Community-based studies on Islamic guidance and counseling have predominantly focused on formal institutional settings, such as schools and youth organizations, leaving the dynamics of non-formal moral character development in rural communities involving multiple community actors relatively underexplored. This qualitative descriptive study addresses this gap by examining how Islamic guidance and counseling practices foster adolescents' moral character in Tallung Ura Village, Enrekang Regency. Data were collected through observations, in-depth interviews, and document analysis involving religious leaders, village officials, parents, and adolescents. The study aims to identify the guidance methods employed, examine the challenges faced by adolescents, and assess the effectiveness of the approaches implemented. The findings indicate that conventional collective approaches based on sermons have gradually been complemented by situational-personal interventions, including direct admonition, individual dialogue, and community-based social control, which appear to be more effective in addressing gadget addiction and peer pressure than one-way preaching alone. The study proposes a community-based Islamic counseling model that integrates religious, familial, and communal dimensions. The findings also highlight the importance of integrating confidential individual counseling services into village-level policies as a complement to traditional sermon-based approaches.